An Electrocatalytic Strategy for Dehydrogenative [4 + 2] Cycloaddition over a Cobalt‐Based Catalyst. Issue 23 (9th September 2022) - Xue, Xiaomeng; Wang, Ye; Zhou, Lina; Ge, Ruixiang; Yang, Jiangrong; Kong, Xianggui; Xu, Ming; Li, Zhenhua; Ma, Lina; Duan, Haohong
Comprehensive Summary: Exploring the anodic reaction to substitute conventional oxygen evolution reaction (OER) for the synthesis of complex pharmaceutical molecules is highly attractive. Here, we report an electrocatalytic strategy for dehydrogenative [4 + 2] cycloaddition of N, N ‐dialkylanilines with maleimides via dual functionalization of both C(sp 3 )‐H and C(sp 2 )‐H bonds, by using an electrochemically activated cobalt carbonate hydroxide hydrate supported on carbon cloth (CCHH‐A/CC), affording various tetrahydroquinolines with high yields. This electrochemical transformation proceeds with high activity and stability, as well as good substrate compatibility. Mechanism study shows that α‐aminoalkyl radical exists in the electrooxidation reaction. This strategy shows significant potential for the synthesis of valuable chemicals by using an electrocatalytic strategy. Abstract : We report an electrocatalytic strategy for dehydrogenative [4 + 2] cycloaddition of N, N ‐dialkylanilines with maleimides via dual functionalization of both C(sp 3 )‐H and C(sp 2 )‐H bonds, by using an electrochemically activated cobalt carbonate hydroxide hydrate supported on carbon cloth (CCHH‐A/CC), affording various tetrahydroquinolines with high yields.